Effects of different Zn2+ levels on antioxidant activity, fatty acid composition, and related gene expression in Phaeodactylum tricornutum - Ma, Ning; Su, Qingling; Song, Pu; Dong, Shaokun; Qiao, Hongjin; Xu, Yingjiang (Frontiers in Marine Science, 2025)
The present study was undertaken to examine the impact of varying concentrations of divalent zinc cation (Zn2+) on the growth, antioxidant levels, fatty acid composition, and related gene expression in a pennate diatom, Phaeodactylum tricornutum. As a prevalent environment contaminant, zinc is introduced into aquatic ecosystems via agricultural and industrial processes, exerting toxic effects on aquatic biota. P. tricornutum was exposed to gradient Zn2+ concentrations (0.99–1000.23 μM), with growth tracked spectrophotometrically. Antioxidant biomarkers, fatty acid profiles, and Zn-responsive gene expression were analyzed via biochemical assays, gas chromatography, and qRT-PCR, respectively. The results showed that appropriate concentrations of Zn2+ were essential for the growth of P. tricornutum, but high concentrations of Zn2+ (1000.23 μM) significantly inhibited its growth. Zinc stress also led to the production of reactive oxygen species (ROS), which in turn triggered oxidative stress, as evidenced by changes in antioxidant enzyme activities and lipid peroxidation levels. Furthermore, zinc stress affected the fatty acid composition of P. tricornutum, particularly in the group exposed to high concentrations of Zn2+. There was a notable reduction in the levels of polyunsaturated fatty acids (PUFAs) and highly unsaturated fatty acids (HUFAs), while the levels of saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) increased. Gene expression analyses indicated alterations in the expression of zinc transporter proteins and antioxidant-related genes, suggesting that P. tricornutum adapts to zinc stress through the regulation of gene expression. These findings provide new insights into the understanding of the physiological and molecular responses of microalgae to zinc pollution and a scientific basis for evaluating the potential impacts of zinc pollution on aquatic ecosystems and developing bioremediation strategies.